The reception of Ariosto's Orlando furioso (1532) by three Italian women writers of the sixteenth century - Waring, CIM (2006)
The thesis aims to bridge a gap in the current re-evaluation of women’s contribution to the literature of Renaissance Italy, by focussing on the reception of Ariosto’s epic poem Orlando Furioso - published in its ‘final’ version in 1532 - by three female poets of the sixteenth century: Isabella di Morra (1516/18-45/46), Laura Bacio Terracina (c.1519-77) and Moderata Fonte (1555-92). The thesis examines how the ‘Ariostism’ of all three women writers challenges the model of Petrarch as benchmark for female literary production during the Cinquecento. Chapter One outlines some of the gender-related issues raised in the Furioso, with which the three female poets may subsequently be said to engage. The chapter looks at both narratorial statements and constructions of masculinity and femininity within the text, revealing Ariosto’s complex relationship with the question of gender. Chapter Two considers the Ariostan echoes present within Isabella di Morra’s Rime, first published in full in an anthology of 1559. Her small canzoniere - not typically Petrarchan in its themes and tone - is re-considered in light of the Furioso, especially with regard to the topos of the ‘abandoned woman’ and the twin themes of harsh landscape and malevolent Fortune which are central to her poetics. Chapter Three discusses Laura Bacio Terracina’s Discorso sopra tutti i primi canti d’Orlando Furioso (1549), a moralizing commentary in ottava rima which constitutes one of the most direct responses to Ariosto’s poem. Terracina’s bold appropriation of the model of the Furioso incorporates aims of both a poetic and an ideological nature, since her engagement also revolves around moral issues that are mostly gendered in their emphasis. Chapter Four considers Moderata Fonte’s Tredici canti del Floridoro (1581), the first ‘original’ romance epic to be written and published by a woman. The Floridoro contains strong thematic and structural parallels with the Furioso; yet the chapter also highlights the ways in which Fonte diverges from the Ariostan precedent re-writing the epic genre in feminine - and ‘feminist’ - key. The thesis concludes that the poetic model of the Furioso would play an increasingly important role in the development of the female literary canon as the century progressed.